2000
DOI: 10.1139/y99-131
|View full text |Cite
|
Sign up to set email alerts
|

Food intake regulation in rodents: Y5or Y1NPY receptors or both?

Abstract: Neuropeptide Y (NPY), one of the most abundant peptides in rat and human brains, appears to act in the hypothalamus to stimulate feeding. It was first suggested that the NPY Y1 receptor (Y1R) was involved in feeding stimulated by NPY. More recently a novel NPY receptor subtype (Y5R) was identified in rat and human as the NPY feeding receptor subtype. There is, however, no absolute consensus since selective Y1R antagonists also antagonize NPY-induced hyperphagia. Nevertheless, new anti-obesity drugs may emerge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Stimulation of food intake by central injections of NPY Y1 and Y5 agonists (12,38), inhibition of NPY-and fasting-induced increases in food intake by central injections of NPY Y1 and Y5 receptor antagonists (14,43), or injections of antisense oligonucleotides directed at these receptors (27) strongly implicate their involvement in NPY-induced hyperphagia, but not without some controversy (30). Nevertheless, collectively it appears that both of these receptors are involved in NPY-induced increases in food intake in laboratory rats and mice (18). In the present study, the Y5 receptor subtype seems considerably more closely linked to feeding, especially by hamsters in the 10 revolutions/pellet and blocked wheel groups, whereas the Y1 receptor agonist had virtually no effect on food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of food intake by central injections of NPY Y1 and Y5 agonists (12,38), inhibition of NPY-and fasting-induced increases in food intake by central injections of NPY Y1 and Y5 receptor antagonists (14,43), or injections of antisense oligonucleotides directed at these receptors (27) strongly implicate their involvement in NPY-induced hyperphagia, but not without some controversy (30). Nevertheless, collectively it appears that both of these receptors are involved in NPY-induced increases in food intake in laboratory rats and mice (18). In the present study, the Y5 receptor subtype seems considerably more closely linked to feeding, especially by hamsters in the 10 revolutions/pellet and blocked wheel groups, whereas the Y1 receptor agonist had virtually no effect on food intake.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the utility of receptor knockout mice to define the molecular mode of action of drugs cannot be overemphasized. The mechanism of action by which other NPY Y5 antagonists (47,48) reported to produce marked hypophagic effects in rodents is unknown, but notably no data have been presented to indicate that antagonism of NPY Y5 is their primary mode of action. We believe that the present data show convincingly that NPY5RA-972 potently antagonizes NPY Y5 receptors in the brain but fails to affect feeding in a variety of rat feeding models.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study of the effects of a selective NPY Y1 antagonist in NPY-treated wild-type, NPY Y1-deficient, and NPY Y5-deficient mice provides compelling evidence for the involvement of NPY Y1 in NPY-induced feeding (55). A number of other groups have shown that selective NPY Y1 antagonism inhibits NPY-induced feeding in rats (12,13,38,48).…”
Section: Discussionmentioning
confidence: 99%
“…It may turn out that combinations of NPY receptor antagonists represent the best approach to the modulation of the complex sequence of physiological and behavioral events that underlie normal and disordered appetite. 169 Clearly, care will also have to be exercised in the extrapolation of animal data using NPY antagonists to humans, where each NPY receptor subtype may have a different distribution and function. Therefore, the final answer as to whether any NPY receptor antagonist will be useful in the control of food intake, without producing unacceptable side effects, can only be definitively answered by clinical studies in man.…”
Section: Discussionmentioning
confidence: 99%